Biodiversity and environmental characteristics of the bycatch assemblages from the tropical tuna purse seine fisheries in the eastern Atlantic Ocean. (16th August 2018) - Lezama‐Ochoa, Nerea; Murua, Hilario; Ruiz, Jon; Chavance, Pierre; Delgado de Molina, Alicia; Caballero, Ainhoa; Sancristobal, Igor
Abstract: The impact of human activities such as fishing has been identified as a main factor in diversity loss in the open ocean. This paper studies the diversity patterns and environmental characteristics of the bycatch assemblages in Fish Aggregating Devices (FADs) and Free School sets (sets made on schools of tuna) from the tropical tuna purse seine fishery in the eastern Atlantic Ocean (35°W–15°E and 20°N–15°S). Data were collected from scientific observer programmes carried out between 2003 and 2011 on board Spanish and French fleets. The results showed different structure and diversity patterns of the bycatch assemblages depending on the fishing mode, with higher number of species and diversity found in FAD sets than in Free School sets. Bycatch assemblages showed preferences for specific oceanographic characteristics of the Atlantic Ocean, such as the equatorial and seasonal coastal upwelling systems, the Cape Lopez front system and the Guinea dome. The type of set and sea surface temperature play an important role to describe the diversity patterns of these species. These results confirm the importance of integrating different methods to study the marine ecosystem towards the correct implementation of the Ecosystem Approach to Fishery Management (EAFM).